WOMEN'S LANGUAGE FEATURES USED BY MAIN CHARACTER IN JOY MOVIE BY DAVID O. RUSSEL - Fardiah Amalia Ardani; Ali Ajam; Samsudin Hi Adam (Universitas Khairun, 2023)
This study aims to determine women's language features used by the main character in the Joy movie based on Lakoff's theory. This study uses a descriptive qualitative method. More specifically, the researcher used the theory of Miles, Huberman Saldana (2014) which consists of data condensation, data display, and conclusion drawing/verification to analyze the data and describe the findings. Data sources were collected from the utterances of the main character from the movie. The findings show that there are nine out of ten women's language features used by the main character in the movie. They were lexical hedges or fillers, tag questions, rising intonation on declarative, empty adjective, intensifiers, hypercorrect grammar, superpolite forms, avoidance of strong swear words, and emphatic stress. While precise color terms are not found in the movie.